THIN-LAYER DRYING OF SPINACH LEAVES IN A CONVECTIVE DRYER - Doymaz, Ibrahim (WILEY-BLACKWELL PUBLISHING, INC, 2009)
In the present work, spinach samples were dried using a pilot-scale cabinet-type convective dryer. Drying experiments were conducted using a constant air velocity of 1.2 m/s and four drying air temperatures of 50, 60, 70 and 80C. Drying rate increased with the increase in air temperature and thus reduced the drying time. The experimental drying data of spinach were applied to four moisture ratio models, namely, the Henderson and Pabis, Lewis, Page, and logarithmic models. Nonlinear regression analysis was performed to relate the parameters of the model with the drying conditions. The performance of these models is evaluated by comparing the coefficient of determination, R(2), and the reduced chi-square, chi(2), between the observed and predicted moisture ratios. Among all the models, the logarithmic model was found to be the best for explaining the drying characteristics of spinach leaves. The effective moisture diffusivity varied from 6.590 x 10(-10) to 1.927 x 10(-9) m(2) /s over the temperature range studied, with an activation energy of 34.35 kJ/mol for spinach leaves.
Keywords: KINETICS; SLICES; REHYDRATION; MICROWAVE; BEHAVIOR; QUALITY; TEMPERATURES; POTATO; FOODS; ONION; Engineering; Food Science & Technology